Modest radiation dose escalation for early-stage anal cancer: cancer control and toxicity outcomes - Copling, Sage; Rooney, Michael K.; Das, Prajnan; Koay, Eugene J.; Ludmir, Ethan B.; Minsky, Bruce D.; Noticewala, Sonal S.; Smith, Grace L.; Holliday, Emma B. (Frontiers in Oncology, 2025)
BackgroundThe optimal dose for patients with early-stage squamous cell carcinoma of the anus (SCCA) is unknown. We aimed to evaluate the impact of modest dose escalation (54 Gray (Gy)) compared with standard dose (50 Gray) on the disease-free survival and toxicity outcomes for patients with T1-2N0 SCCA.MethodsPatients with T1-T2N0 SCCA treated with definitive radiation from 1/1/2003 until 6/31/2022 were included in this retrospective analysis. Regression discontinuity analysis was performed to evaluate for a potential causal effect of modest dose escalation on freedom from local recurrence (FFLR). Cox proportional hazards model was generated to estimate the effect of modest dose escalation on FFLR, and an additional analysis was performed restricting the dataset to individuals with tumors measuring 1.5-2.5cm. Ordinal logistic regression was used to identify factors associated with several graded toxicity outcomes including acute and late gastrointestinal (GI), genitourinary (GU), dermatologic, and acute pain toxicities.ResultsTwo hundred thirty-four patients with T1N0 (N = 85, 36%) or T2N0 (N = 149, 64%) SCCA were included. Eighty-four (35.9%) received 50 Gy, 147 (62.8%) received 54Gy and 3 (1.3%) received 54–55 Gy. The median [IQR] time from the end of radiation to last follow up was 78 [44-119] months. Two- and 5-year FFLR were 90.7% and 88.6%. There was no significant association between modest dose escalation and FFLR (HR 0.6, 95% CI 0.2-1.9, P = 0.4) in patients with tumors 1.5-2.5 cm. In the global multivariable Cox regression model including all 234 patients, only positive HIV status (HR 5.2 [95% CI 1.2-21.5], P = 0.02) persisted as a significant predictor of worse FFLR on multivariate analysis. Modest dose escalation (P = 0.3) and tumor size (P = 0.6) did not predict FFLR. Modest dose escalation was associated with worse acute GU toxicity (OR 3.28, 95% CI 1.40-8.59, p = .01) and worse acute pain toxicity (OR 3.63, 95% CI 2.03- 6.65, p <.001).ConclusionsModest dose escalation was not associated with improved FFLR among patients with T1-2N0 SCCA; however, it was associated with worse acute GU and pain toxicity. Future efforts should focus on biomarkers to identify patients who may potentially benefit from treatment escalation.